Near total extirpation of vestibular schwannoma with salvage radiosurgery. (13th January 2015) - Jeltema, Hanne Rinck; Bakker, Nicolaas A.; Bijl, Hendrik P.; Wagemakers, Michiel; Metzemaekers, Jan D. M.; van Dijk, J. Marc C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The management of a sporadic vestibular schwannoma (VS) has changed with the introduction of stereotactic radiosurgery (SRS). Because functional outcome is important, particularly regarding the facial nerve, a policy of near‐total surgical resection of a large‐size VS has emerged, minimizing damage to the facial nerve. The debate remains whether the surgical remnant should be treated immediately or after established growth. Study Design Retrospective case series. Methods A consecutive cohort of 55 patients underwent a retrosigmoid craniotomy and near‐total removal of a large‐size VS at our university medical center between 2005 and 2011 and had a follow‐up of a least 3 years. Documented growth of the VS remnant after surgery necessitating adjuvant SRS was the primary outcome measure using analysis of variance. Results In 45 patients (81.8%), a small tumor remnant was left during surgery. The mean preoperative tumor volume was 12.2 cm3 (range, 1.13–50.16 cm3); the mean volume of the remnant was 0.22 cm3 (range, 0–1.52 cm3). The mean postoperative follow‐up time was 35.4 months (range, 3–76 months). Salvage SRS was deemed necessary in seven patients (13.0%). The size of the postoperative tumor remnant was a significant predictor for the necessity of postoperative adjuvant SRS. Normal facial nerve function (House‐Brackmann [HB] I) was preserved in 30 patients (57.7%), 17 patients (32.7%) experienced a permanent mild facial nerve deficit (HB II, III), and five patients (9.6%) experienced a severe facial nerve deficit (HB grade IV–VI). Conclusions Initial observation after near total surgical removal of VS is a feasible strategy, with only a minority requiring salvage radiosurgery during follow‐up. Level of Evidence 4. Laryngoscope, 125:1703–1707, 2015